2023
DOI: 10.3390/catal13071028
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Dual Z-Scheme CuBi2O4/Bi2Sn2O7/Sn3O4 Photocatalysts with Enhanced Photocatalytic Performance for the Degradation of Tetracycline under Visible Light Irradiation

Abstract: The dual Z-scheme heterojunction CuBi2O4/Bi2Sn2O7/Sn3O4(CBS) was successfully constructed through in situ growth methods, and its photocatalytic performance was evaluated via degradation of tetracycline hydrochloride under visible light. Out of all samples, CBS-2 exhibited the highest photocatalytic activity, with an apparent rate constant of 2.34, 20.16, and 44.17 times that of Bi2Sn2O7, CuBi2O4, and Sn3O4, respectively. Even after four cycles, the photocatalytic efficiency remained above 85%. The improvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Antibiotics are chemicals that are used to treat infections caused by bacteria and for livestock production. Particularly, wastewater from hospitals and pharmaceutical companies ares the primary sources of antibiotics. , Hence, their accumulation in the environment hurts ecosystems. The elimination of antibiotics from the environment using different techniques such as biodegradation, membrane separation, coagulation, and absorption has been re- ported.…”
Section: Bbzsh Photocatalytic Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotics are chemicals that are used to treat infections caused by bacteria and for livestock production. Particularly, wastewater from hospitals and pharmaceutical companies ares the primary sources of antibiotics. , Hence, their accumulation in the environment hurts ecosystems. The elimination of antibiotics from the environment using different techniques such as biodegradation, membrane separation, coagulation, and absorption has been re- ported.…”
Section: Bbzsh Photocatalytic Degradationmentioning
confidence: 99%
“…These changes directly influence the materials’ optical absorption, charge carrier dynamics, surface reactivity, and catalytic performance. The most common methods used to synthesize BBSc photocatalysts include solvothermal/hydrothermal methods, , coprecipitation methods, sol–gel method, , solid-state thermolysis, stepwise deposition techniques, in situ growth, and photoreduction techniques. This work aims to review the recent studies on BBZSH photocatalysts for treating contaminated water.…”
Section: Introductionmentioning
confidence: 99%
“…Six of them focus on photocatalytic materials and processes. Xu et al studied the photocatalytic degradation of tetracycline under visible light irradiation with dual Z-scheme CuBi 2 O 4 /Bi 2 Sn 2 O 7 /Sn 3 O 4 photocatalysts, and found that the construction of the Z-scheme heterojunction could effectively promote the separation and migration of photogenerated carriers [1]. Peng et al prepared a Mn-Co-MCM-41 molecular sieve using a thermo-sensitive template, and showed good catalytic performance on the degradation of RhB [2].…”
mentioning
confidence: 99%